Corruption in the Quranic Perspective An -Analytical Study- - Ali , Hammadi (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to God in good and bad time. We praise God Almighty for showing us good and evil, to be keen on good and its causes, and to avoid evil and its paths, and may God bless him and grant him peace on the one who is sent as a mercy to the worlds and to his family and companions as a whole. The issue of corruption today is one of the most important problems facing the world and impeding its progress. It is a serious scourge that threatens the entity of any society in which it is located, so we tried in this simple research to find out the reality of corruption and its existence, recalling the Holy Qur’an and the Prophet’s Sunnah, and identifying the causes and solutions that can Contribute to reducing it, bearing in mind that our talk about corruption here is in general; especially, to study any part of corruption will take a lot of time.